Proof of the Authenticity of the Holy Quran: Discovering the Precise Mathematical Arrangement in the Sura Fussilat - Benzitouni, Saadane; Benzitouni, Sara (Journal of Quranic Sciences and Research, 2024)
In this article, the numerical structure of the Holy Quran has been studied based on two main sources of the suras, namely the suras numbers and the number of verses. The objective of this study is to prove the authenticity of the Holy Quran using a unique scientific methodology, which will show, through mathematical relations and a system of equations, that the book has been correctly preserved. Firstly, the suras were divided into four groups or tables according to their even and odd numbers, which leads to discover two important properties among the Quranic parameters: the concordance relation and rule 1. The application of the proposed scientific methodology led to the discovery of of a hidden element of concordance, which is sura Fussilat, whose integration into its own Ha-Mim family allowed the discovery of other secondary concordance relations. At the same time, it reveals other important rules that will play an essential role in formulating the system of mathematical equations. Given the diversity of roles played by this sura, we consider it as a key programmed by the author of the book to achieve this amazing mathematical arrangement. The resolution of this system will prove that the total number of suras and the total number of verses have not undergone any change. Therefore, the obtained results confirm that the structure of the Quran remained consistent with the original.